Analysis of Reservations and Guest Handling Complaints on Intention to Revisit the Front Office Department of the Grand Mercure Hotel Jakarta Kemayoran - Kusumaningrum, Anisa Putri; Wahyu, Mochamad Alfaz Subur; Pradini, Gagih (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2025)
This research analyzes Reservations and Guest Handle Complaints on Intention to Revisit the Front Office Department of Grand Mercure Hotel Jakarta Kemayoran. The sample in this research used primary data with data collection methods through questionnaires distributed to 100 respondents. The data analysis technique uses quantitative descriptive analysis. This research shows that reservations have a positive and significant effect on interest in returning to visit, and guest-handler complaints have a positive and significant impact on interest in visiting again. So, the Grand Mercure Jakarta Kemayoran Hotel should provide better service so that the interest in visiting guests at the Grand Mercure Jakarta Kemayoran Hotel continues to increase